Difficult men : behind the scenes of creative revolution : from The Sopranos and The Wire to Mad Men and Breaking Bad /: behind the scenes of creative revolution : from The Sopranos and The Wire to Mad Men and Breaking Bad. (2013) - Martin, Brett, 1972-
No abstract available